2019
DOI: 10.3390/s19051070
|View full text |Cite
|
Sign up to set email alerts
|

Lamb Wave-Minimum Sampling Variance Particle Filter-Based Fatigue Crack Prognosis

Abstract: Fatigue cracks are one of the common failure types of key aircraft components, and they are the focus of prognostics and health management (PHM) systems. Monitoring and prediction of fatigue cracks show great application potential and economic benefit in shortening aircraft downtime, prolonging service life, and enhancing maintenance. However, the fatigue crack growth process is a non-linear non-Gaussian dynamic stochastic process, which involves a variety of uncertainties. Actual crack initiation and growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…10,11 Therefore, the improvement of the resampling and the importance sampling method in particle filtering algorithm has become a research hotspot for researchers. Studies presented in Refs 12,13 are similar to the ones shown in this paper.…”
Section: Introductionsupporting
confidence: 87%
“…10,11 Therefore, the improvement of the resampling and the importance sampling method in particle filtering algorithm has become a research hotspot for researchers. Studies presented in Refs 12,13 are similar to the ones shown in this paper.…”
Section: Introductionsupporting
confidence: 87%
“…The state-space model based on the crack propagation law consists of a state equation and observation equation [28], as shown in Eq. (1).…”
Section: Framework Of the Particle Filter Based On Fatigue Crack Grow...mentioning
confidence: 99%
“…However, the optimal number of particles in the PF algorithm is often difficult to choose. In addition, too many particles will reduce the computational efficiency and affect the real-time prediction of crack growth (Yang and Gao, 2019). By introducing intelligent optimization algorithms into the standard PF algorithm, the particles obtained by a priori sampling can move to the region with high a posteriori probability, and the problem of particle leanness can also be overcome.…”
Section: Introductionmentioning
confidence: 99%